Key characteristics of decision making in soccer and their implications. (April 2021) - Petiot, Grégory Hallé; Bagatin, Rafael; Aquino, Rodrigo; Raab, Markus
Abstract: This paper puts forward the position that the cognitivist approach adopted in research on decision making in team sports leads to a disconnection from the actual environment of play. The argument is structured as a narrative review of 60 articles that were analyzed to identify the most recent concepts related to the following topics or combinations thereof: tactics and action in the play; decision making and associated cognitive mechanisms and skills; and the teaching–learning–training process. The results of the review led us to characterize decision making in the team sports context as being (a) "prereflected, " (b) based on evaluation, (c) frugal, and (d) "generated, " as opposed to being a process of choosing from alternatives. In addition to showing clear adjustments to the environment of play, the four characteristics imply that teaching, learning, and training to play should also be designed according to the restrictions imposed by the context and the actual lived experience of the play. We conclude that cognition should not be considered solely responsible for decisions, and thus both theoretical and pedagogical models of player development should take the ecological perspective of decision making into account. As a result, the methodologies employed to develop players from an early age could be elaborated on by taking into account the interaction between cognitive skills and the possibilities emerging in the play.